ASEAN comprehensive perspective in countering terrorism: Is a common strategy possible? - --, Seniwati; Mohd Sani, Mohd Azizuddin; Eby Hara, Abubakar (2012)
This paper offers insights into how ASEAN (The Association of Southeast Asian Nations) can tackle global issues of terrorism within the international system.The global war on terrorism, to a certain degree, has influenced the ASEAN leaders to securitize terrorism as a critical threat to ASEAN.However, in contrast to some other state which fight terrorism directly by using military forces, ASEAN take a more comprehensive policy by securitizing that issue in the context of transnational security threats that have threatened ASEAN for some time.The securitization has been done through speech-acts and some actions as part of ASEAN efforts to face transnational security threats.Among policies that have been enunciated include: (a) a common declaration to condemn terrorism and to work together to combat terrorism in November 2001; (b)the ASEAN bodies; and (c) several agreements in combating-terrorism, transnational crime or non-traditional security issues made with some countries such as the United States of America and Australia.By using these strategies, are more promising than those taken by some other state that attempt directly to combat terrorism by using military pressures.This paper also suggests that, one important issue that ASEAN should resolve in the context of its comprehensive security strategy is to synchronize their legal approaches to combat terrorism that can make policy coordination to fight terrorism easier to conduct.